Trade agreements, petroleum and energy policies (UN New YorkUS, 2000)
Seeks to assist petroleum-producing countries to preserve their ability, in the context of future trade negotiations, to use their natural energy resources to promote their development and enhance their competitiveness in the world market, while defending and improving market access for their exports within the framework of the World Trade Organization.
Keywords: TRADE AGREEMENTS